Mandatory Reorganization of Corporate Law Entities (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
Relations related to the organization and abolition of subjects of corporate law are important in the context of a market economy. If the organization of subjects of corporate law generates a new subject of law and makes a concrete contribution to economic development along with the emergence of new subjective rights and obligations in economic and legal relations, then their termination will lead to the termination of the subject of law and the termination of the subject's activities in the field of corporate law. economic relations in exchange for This article discusses the reorganization of corporate law entities, the liquidation of a legal entity and the emergence of a new legal entity instead of it or the decision of the future fate of the property.